Penerimaan konsumen dan nilai gizi cendol ikan lele (Clarias batrachus) dengan penambahan serbuk kopi - Novia Anggraeni; Hatmiyarni Tri Handayani (Fakultas Pertanian Universitas Yudharta Pasuruan, 2022)
Cendol is one of the popular drinks in Indonesia which is made from flour with incomplete nutritional content, so it is necessary to modify the formulation of cendol by adding catfish meat and coffee powder to complement the nutritional value of cendol products. The purpose of this study was to determine the effect of adding coffee grounds to consumer acceptance and the nutritional value of catfish cendol products. This study used a completely randomized design (CRD), with 4 additional treatments of coffee powder 0 g, 2 g, 4 g, and 6 g. The results showed that the addition of coffee powder had an effect on the hedonic yield of catfish cendol. The best cendol according to consumer acceptance is based on the results of hedonic code K2 with the addition of 4 g of coffee powder with water content of 65.34%, ash content of 0.48%, fat content of 0.52%, protein content of 11.13%, and carbohydrates 23, 53%.